Fabrication of an In-house Phantom for Evaluation of Metal Artifact Reduction in Computed Tomography (International Journal of Scientific Research in Science and Technology, 2024)
Purpose: This study aims to fabricate an in-house phantom for evaluating effectiveness of a metal artifact reduction (MAR) algorithm in computed tomography (CT) images. Methods: The in-house phantom was made from polyester-resin (PESR) with methyl ethyl ketone peroxide (MEKP) as a catalyst. The dimension of the phantom was 160 mm in diameter and 50 mm in length with seven insert holes ranging from 10 to 20 mm. The titanium representing a metal implant and calcium carbonate representing the bone were inserted into the holes of the phantom. The phantom was scanned using a GE Revolution Apex CT scanner, slice thickness of 1.25 mm, and tube current of 200 and 370 mA. Images were reconstructed using filtered back projection (FBP) and MAR algorithm for reducing metal artifact. Artifact evaluation was characterized by changing in CT number and image noise. Results: Titanium material increases metal artifact in the in-house phantom. Metal artifact from titanium decreases CT number around 5% and increases noise level around 60%. MAR implementation can reduce metal artifacts, which is indicated by an increase in the CT number around 0.7% and a decrease in noise level around 30%. Conclusion: The in-house phantom for evaluating MAR algorithm was successfully developed. The presence of titanium increases metal artifacts, which is characterized by a decrease in the CT number and an increase in noise level in the area around the titanium. It is found that the MAR succeeded in reducing metal artifacts.